Synthesis and Characterization of Metallic Gel Complexes Derived from Carboxymethyl Cellulose - H. D. Juneja; Manisha Joshi; J. P. Kanfade (Journal of Chemistry)
The oxaloyl carboxymethyl cellulose (OCMC) complexes of Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) metal ions have been synthesized and the coordination of OCMC in these complexes has been investigated through IR spectra, reflectance spectra, and thermal analysis. On the basis of spectral and thermal data an octahedral geometry was assigned to [Mn(II)OCMC(H2O)2]n and [Co(II)OCMC(H2O)2]n, square planar geometry was assigned to [Cu(II)OCMC]n, and tetrahedral geometry was assigned to [Ni(II)OCMC]n and [Zn(II)OCMC]n Metallic Gel complexes.